2009
DOI: 10.1002/aic.11849
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral patterns of drop impingement onto rigid substrates with a wide range of wettability and different surface temperatures

Abstract: This article concerns behavioral patterns of droplet impingement onto solid substrates covering a wide range of wettability from hydrophilic to superhydrophobic surfaces heated at different temperatures. For droplet impingement onto partial hydrophobic surfaces (mirror-polished Cu substrate), the maximum heights of receding droplet undergoing a consecutive increment with surface temperature can be explained taking account of Marangoni flow. Also, the relation to predict the increment of droplet heights with su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…In this study, we observe and record the dynamics of droplets of various fluid properties as they impact against a rigid solid dry surface at different inclination angles, at pressures ranging from 0.2 to 6 atm. Although they are known to influence impact dynamics, the influence of surface wettability and temperature on splashing threshold was assumed to be small relative to other factors (Li et al, 2009). On the basis of the experimental results, we develop an empirical expression to predict the threshold of splashing that uses the balance between the droplet internal pressure and the droplet surface tension while considering K-H instability and gas pressure.…”
Section: Rementioning
confidence: 99%
“…In this study, we observe and record the dynamics of droplets of various fluid properties as they impact against a rigid solid dry surface at different inclination angles, at pressures ranging from 0.2 to 6 atm. Although they are known to influence impact dynamics, the influence of surface wettability and temperature on splashing threshold was assumed to be small relative to other factors (Li et al, 2009). On the basis of the experimental results, we develop an empirical expression to predict the threshold of splashing that uses the balance between the droplet internal pressure and the droplet surface tension while considering K-H instability and gas pressure.…”
Section: Rementioning
confidence: 99%
“…Significant interest in the interaction between droplets and superheated solid surfaces is evident by the plethora of publications in the last few years [1,2,3,4,5,6,7,8,9,10]. Droplet impingement is present in a wide array of applications including spray cooling, coating, biochemical reactions and combustion, and is the focus of this paper.…”
Section: Introductionmentioning
confidence: 99%
“…The maximum spread diameter, D max , at the LFP provides insight to the dynamics of the system as well and has been explored in multiple previous works [9,20,21,22,23]. Tran et al showed that D max is larger at the LFP on a hydrophilic surface than on a superhydrophobic surface maintained at room temperature for We < 1000, although both exhibit similar spreading/retracting dynamics [12].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations